2016
DOI: 10.1071/rd14348
|View full text |Cite
|
Sign up to set email alerts
|

Lactation-induced changes in metabolic status and follicular-fluid metabolomic profile in postpartum dairy cows

Abstract: The aim was to investigate the effect of lactation on the composition of pre-ovulatory follicular fluid (FF). Forty in-calf primiparous heifers and 20 maiden heifers were enrolled. Immediately after calving, half of the cows were dried off while the remainder were milked twice daily. Serum samples were collected twice weekly from two weeks pre- to 84 days postpartum (dpp). FF was analysed by gas chromatography-mass spectrometry. Serum concentrations of non-esterified fatty acids and β-hydroxybutyrate were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 30 publications
4
51
1
Order By: Relevance
“…Indeed, 97% of cows experienced a weight loss prior to oocyte collection, with only one cow gaining weight immediately pp that produced negligible amounts of milk and was excluded from further analysis. Therefore, most of the cows in the present study behaved consistently with a negative energy balance as it has been described in other studies 4,20 . Furthermore, cows were selected based on additional criteria including energy balance and metabolic level.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, 97% of cows experienced a weight loss prior to oocyte collection, with only one cow gaining weight immediately pp that produced negligible amounts of milk and was excluded from further analysis. Therefore, most of the cows in the present study behaved consistently with a negative energy balance as it has been described in other studies 4,20 . Furthermore, cows were selected based on additional criteria including energy balance and metabolic level.…”
Section: Discussionsupporting
confidence: 89%
“…First, the relationship between plasma glucose and uterine luminal fluid glucose levels is not known; Leane et al (2018) detected no difference in uterine luminal fluid glucose levels between the glucose infusion and control (saline infusion) groups. Second, the baseline plasma glucose levels of lactating cows in this study were already at the higher level reported for heifers or nonlactating cows in previous studies (Maillo et al, 2012;Garverick et al, 2013;Forde et al, 2016), suggesting that the glucose infusion that increased levels by ~10 mg/dL in Leane et al (2018) did not really address an insufficiency. Irrespective, it remains quite surprising that glucose infusion did not affect plasma insulin and nonesterified fatty acids, as could be anticipated in late-lactating dairy cows.…”
contrasting
confidence: 57%
“…Green et al (2012) examined the effects of lactation on early postpartum nutrient partitioning and the establishment of pregnancy and reported that increased likelihood of pregnancy after first insemination was associated with greater blood glucose and IGF1 during the first 30 d postpartum (Green et al, 2012). Consistent with these studies, circulating glucose concentrations were greater in heifers (Forde et al, 2016) and postpartum nonlactating dairy cows (Maillo et al, 2012;Forde et al, 2016) than in postpartum lactating cows. Collectively, these studies indicate a clear association between greater glucose concentrations and improved fertility performance.…”
Section: Discussionmentioning
confidence: 80%
“…Infusion of exogenous glucose elevated blood glucose concentrations by approximately 0.55 mM, a physiologically relevant increase. For example, Maillo et al (2012) and Forde et al (2016) reported blood glucose concentrations of approximately 4 mM for heifers and nonlactating cows and approximately 3.5 mM for lactating cows. This 0.5 mM difference between "fertile" and "less fertile" animals is consistent with the difference between groups in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation